Peningkatan Kapasitas Tata Kelola Laboratorium Melalui Webinar Standar Pelayanan Publik Laboratorium MIPA - Lodwyk N. Krimadi; Yuliana R. Yabansabra; Fernandes J.P. Bonay; Himawan Himawan; Supeno Supeno; Frans A. Asmuruf; Johnson Siallangan; Alowisya Futwenbun (JURNAL PENGABDIAN PAPUA, 2026)
Science laboratories play a strategic role in supporting education, research, and community service; therefore, they require professional governance based on public service standards. This community service program aimed to enhance participants' capacity to understand and implement public service standards in science laboratory management as an effort to prevent maladministration and to promote professional, transparent, accountable, and user-oriented services. The program employed an educational participatory approach through an online webinar consisting of preparation, material presentation, interactive discussion, and evaluation using a Likert scale questionnaire. The results demonstrated an improvement in participants' understanding of public service principles, laboratory service standards, complaint management, the role of laboratories in supporting the Tri Dharma of higher education, and strategies for preventing maladministration through the implementation of public service standards and good laboratory governance. Evaluation of 33 respondents showed that 87.88% were very satisfied, 9.09% were satisfied, and 3.03% were moderately satisfied. The combined satisfaction rate reached 96.97%, with an overall satisfaction index of 89.09%. It can be concluded that the webinar effectively enhanced participants' capacity to strengthen laboratory governance based on public service standards as an effort to prevent maladministration.